Edukasi Pemenuhan Hak-Hak Anak Oleh Orang Tua Dalam Mencegah Kekerasan, Penelantaran Dan Diskriminasi Terhadap Anak - Nurhafni; Nofil Gusfira; Sutri Helfianti; Miftahul Jannah (JKA, 2025)
Violence, neglect, and discrimination against children are serious issues that require special attention from various parties, especially parents. This article discusses the importance of educating parents about fulfilling children's rights as a preventive measure to combat various forms of violence and unfair treatment against children. Through a qualitative approach, this study explores parents' understanding of children's rights and how this knowledge can be applied in daily life. The findings indicate that adequate education can enhance parents' awareness of the importance of respecting and fulfilling children's rights, encouraging them to create a safe and supportive environment for their children's development. Additionally, the article provides recommendations for educational institutions and communities to develop programs that support parents in understanding and implementing children's rights. Thus, it is hoped that educating parents about children's rights can contribute to preventing violence, neglect, and discrimination, ultimately creating a healthier and more competitive generation.